2011
DOI: 10.1007/s12291-011-0132-4
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein and Uric Acid Levels in Patients with Psoriasis

Abstract: Serum CRP and uric acid levels were estimated in twenty-five patients with psoriasis (group III) before and after 12 weeks of treatment. Results were compared with a group of 25 normal subjects (group I) and a group of 25 patients of various skin diseases other than psoriatic lesion (group II). Mean value for CRP was found to be increased by more than 20 folds in patients with psoriasis, which was subsequently reduced to nearly 50% of the initial value after 12 weeks of treatment. These patients also showed hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 10 publications
9
43
1
3
Order By: Relevance
“…Furthermore, increased concentration of uric acid was accompanied by increased serum level of C-reactive protein. [202]. Hyperuricemia has also been reported in psoriatic arthritis [203].…”
Section: Uric Acidmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, increased concentration of uric acid was accompanied by increased serum level of C-reactive protein. [202]. Hyperuricemia has also been reported in psoriatic arthritis [203].…”
Section: Uric Acidmentioning
confidence: 92%
“…It has been suggested that serum uric acid should be monitored in patients with psoriasis and metabolic syndrome [200][201][202]. However, a prospective study is required in order to determine if the prevention or treatment of hyperuricemia may affect the development of metabolic syndrome or the course of psoriasis.…”
Section: Uric Acidmentioning
confidence: 99%
“…Our findings are in concordance with that of several previous studies conducted separately and involving relatively small patient populations. 6,11,13 According to them enhanced inflammation induces the development of atherogenic dyslipidemic profile in psoriasis patients by modulating the lipoprotein lipase activity via antilipoprotein lipase antibodies. In addition, atherogenic complexes of autoantibodies to oxidized LDL are generated in response to an oxidative inflammatory effect which enhances the accumulation of LDL in the endothelial wall and thereby enhances the CVD risk in psoriasis patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as best of our knowledge, previous studies on psoriasis patients have not included systemic inflammation, oxidative stress and dyslipidemia in a single setting. [11][12][13] Therefore, the present work aims to evaluate the levels of c-reactive protein (CRP), MDA, lipid profile and Apo B/A1 ratio in active psoriasis patients and to determine their role in prediction of CVD risk in same population.…”
Section: Introductionmentioning
confidence: 99%
“…C-reactive protein -CRP) i kwasu moczowego w surowicy u pacjentów z łuszczycą przed leczeniem i po 12 tygodniach terapii. Po zastosowaniu leczenia stę-żenie CRP zmniejszyło się o 50%, a redukcja stężenia kwasu moczowego nastąpiła u prawie 80% pacjentów [48]. Powyższe obserwacje dały podstawy do sformułowania teorii, że łuszczyca, która jest chorobą związaną ze zwiększeniem szybkości proliferacji komórek naskórka (ang.…”
Section: Kwas Moczowy a łUszczycaunclassified